Development of heterogeneous catalysts for transesterification of non-edible oil to biodiesel - Lee, Hwei Voon (2012)
The critical problem arises from the fossil fuels has stimulated recent interests in alternative sources for petroleum-based fuel. An alternative fuel should be technically feasible, readily available, environment acceptable and techno-economically competitive. Biodiesel, which is considered as a potential replacement of conventional diesel fuel is commonly, composed of mono-alkyl ester of long chain that can be prepared from triglycerides which is available in renewable feedstock (vegetable oils or animal fats) utilizing transesterification technology. The feedstock used for the production of biodiesel mainly come from edible vegetable oil which is highly available in most of the countries around the world. However, the competition between food and fuel economies towards the same oil resources may bring global imbalance to the food supply and demand market. The focus on this research is to produce biodiesel using non-edible feedstock (Jatropha Curcas oil) via heterogeneous catalyzed transesterification reaction. The solid base mixed metal oxide catalysts (CaO-MgO, CaO-ZnO, MgO-ZnO and CaOLa2O3) were synthesized via co-precipitation method. The physico-chemical properties of binary oxide catalysts were characterized by using X-ray diffraction (XRD), temperatureprogrammed desorption of carbon dioxide (CO2-TPD), temperature- programmed desorption of ammonia (NH3 -TPD), scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDX), N2 adsorption (BET), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and atomic absorption spectroscopy (AAS). Furthermore, the catalytic activity of mixed metal oxides with different stoichiometric ratios (0.5- 10.0 atomic ratio) of Ca/Mg, Ca/Zn, Mg/Zn and Ca/La corresponding to CaOMgO, CaO-ZnO, MgO-ZnO and CaO-La2O3, respectively, was investigated. The optimum ratios for each binary metal oxides catalyst with highest activity were CaOMgO with 0.5 atomic ratio (90 %), CaO-ZnO with 8.0 atomic ratio (94 %), MgO-ZnO with 8.0 atomic ratio (83 %) at transesterification temperature of 120 oC, 25 methanol/oil molar ratio, 3 wt.% of catalyst loading within 3 h reaction time. Whereas, CaO-La2O3 with 8.0 atomic ratio (98 %) showed the highest activity among the series at 160 oC reaction temperature, 25 methanol/oil molar ratio, 3 wt.% of catalyst loading and 3 h reaction time. The transesterification activity was greatly influenced by the basicity of the active site on the catalyst. Optimization study for jatropha-based biodiesel production using CaO-MgO, CaO-ZnO, CaO-La2O3 and MgO-ZnO mixed oxides solid base catalysts was conducted in this study. The effects of variables including reaction temperature (40-200 oC), catalyst loading (1-5 wt. %), methanol/oil molar ratio (15-30) and reaction time (1-5 h) on biodiesel yield was examined and optimized using response surface methodology (RSM) coupled with central composite design (CCD). Confirmation experiment was further conducted to validate the efficacy of the model. The CaO-MgO, CaO-ZnO, MgO-ZnO and CaO-La2O3 catalyzed reaction model generated from RSM showed reasonable predictability and sufficient accuracy of the examined catalyzed reaction. Furthermore, the physical and chemical characteristics of the jatropha-based biodiesel produced from CaO-MgO, CaO-ZnO, MgO-ZnO and CaO-La2O3 catalyzed transesterification reaction was tested with compliance to ASTM D7851 and EN 14124 standards.